Culture-bound syndromes in migratory contexts: the case of Bolivian immigrants - María Teresa Roldán-Chicano; José Fernández-Rufete; César Hueso-Montoro; María del Mar García-López; Javier Rodríguez-Tello; María Dolores Flores-Bienert
ABSTRACT Objective: to describe the culture-bound syndromes maintained by Bolivian immigrants in the new migratory context and analyze the care processes of these health problems. Method: qualitative research with an ethnographic methodological approach. Sample: 27 Bolivian immigrants. In-depth interviews and participatory observation were the strategies used for data collection. Data were classified and categorized into logical schemes manually and using the ATLAS-ti program v.5. Results: susto, "wayras", amartelo, pasmo de sol, pasmo de luna and pasmo de sereno are some of the folk illnesses that affect the Bolivian immigrants and that they have to treat in the new migratory context. Conclusions: in the new environment, the group under study preserves culture-bound syndromes that are common in their country of origin. The care strategies used for these health problems are adapted to the resources of the new context and based on interactions with the domestic environment, biomedicine and traditional medicine. It was observed the need for the health professionals to realize that the efficacy of certain therapies occurs within the scope of cultural beliefs and not in that of the scientific evidence.